Longitudinal health‐related quality of life in first‐line treated patients with chronic lymphocytic leukemia: Results from the Connect® CLL Registry. Issue 1 (26th July 2020) - Sharman, Jeff P.; Cocks, Kim; Nabhan, Chadi; Lamanna, Nicole; Kay, Neil E.; Grinblatt, David L.; Flowers, Christopher R.; Davids, Matthew S.; Kiselev, Pavel; Swern, Arlene S.; Sullivan, Kristen; Gharibo, Mecide M.; et al.
Abstract: Health‐related quality of life (HRQoL) in patients with chronic lymphocytic leukemia (CLL) is important in guiding treatment decisions. However, the impact of CLL treatment initiation on HRQoL is unclear. We assessed HRQoL using the FACT‐Leu and EQ‐5D‐3L questionnaires in the Connect ® CLL Registry, a large, US‐based, multicenter, prospective observational study of CLL patients enrolled between 2010 and 2014, prior to the introduction of novel therapies. Among 889 patients initiating first‐line therapy with chemoimmunotherapy or rituximab monotherapy, questionnaire completion rates were 95.7% and 95.8% at enrollment, and 70.8% and 69.4% at 12 months, for FACT‐Leu Total and EQ‐5D‐3L, respectively. For 849 patients completing all five FACT‐Leu components, average total scores were 135.7 at enrollment and 141.6 at 12 months. Among 526 patients with FACT‐Leu Total scores at enrollment and 12 months, clinically meaningful (≥11‐point) improvements or reductions were observed in 179 (34.0%) and 88 (16.7%) patients, respectively. Mean EQ‐5D‐3L index scores were 0.87 at enrollment and 12 months. Among 513 patients completing EQ‐5D‐3L at enrollment and 12 months, clinically meaningful (≥0.06‐point) improvements or reductions were observed in 125 (24.4%) and 116 (22.6%) patients, respectively. In the Connect ® CLL Registry, HRQoL remained stable or slightly improved after 12 months of follow‐up.